The Role of Influencers and Digital Marketing On Shopping Emotion In The Millennial Generation In Digital Era - Anak Agung, Elik Astari; Ni Luh, Kardini; Ni Made , Rini Desiyanti (Terbuka Journal of Economics and Business, 2023)
The mobility of the millennial generation has become one of the centers of economic attention, both from how to make money to how to spend money. This phenomenon is of course read by entrepreneurs in increasing shopping emotion. Several studies have proven that shopping emotions are not only influenced by influencers but also digital marketing. The aim of this research is to determine the role of influencers and digital marketing on shopping emotions in the millennial generation in the new normal era. This research was conducted on the millennial generation in Bali using a questionnaire as a research data collection method. The number of samples used was 50 respondents using a non-probability sample research method (purposive sampling). The analysis technique used is multiple linear regression analysis. The coefficient of determination test result is 76.3%, the shopping emotion variable can be explained by the influencer and digital marketing variables. The remaining 23.7% is explained by other variables outside the model. The results of this research are that the role of influencers and digital marketing partially has a positive and significant effect on shopping emotion. And the simultaneous relationship between digital marketing will have a positive effect if it is balanced with the role of influencers in increasing the positive emotions of the millennial generation towards shopping emotions.